1993
DOI: 10.1007/bf00040405
|View full text |Cite
|
Sign up to set email alerts
|

Variation in resistance of Mexican landraces of maize to maize weevil Sitophilus zeamais, in relation to taxonomic and biochemical parameters

Abstract: Accessions representing twenty eight landraces of maize were assessed for susceptibility to the maize weevil, Sitophilus zeamais in standardized resistance tests. Susceptibility parameters such as weight loss of grain, number of insect progeny produced, the Dobie index of susceptibility, and oviposition on grain were found to vary significantly by genotype, with exceptional resistance found in accessions representing the Naltel, Chapalote and Palomero landraces. As in improved genotypes, susceptibility was neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
74
2
11

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 13 publications
(14 reference statements)
9
74
2
11
Order By: Relevance
“…It is possible that cationic isozymes were also induced; additional cationic isozymes are present in red oak and are influenced by galling insects in nature (Allison and Schultz, unpublished), but we were unable to resolve them completely on seedling IEF gels. Although the exact functions of anionic isozymes in red oak are unknown, their induction by wounding is consistent with responses to insects (Felton et al, 1992, Arnason et al, 1994, Dowd, 1994Dowd et al, 1998a,b). Anionic PODs have been implicated in a variety of leaftoughening responses, such as lignin biosynthesis (Gaspar et al, 1985;Díaz and Merino, 1998), suberization (Espelie et al, 1986;McDougall, 1993), and crosslinking of cell walls and extensin polymers (Ridge and Osborne, 1970;Everdeen et al, 1988;Bostock and Stermer, 1989).…”
Section: Discussionsupporting
confidence: 60%
“…It is possible that cationic isozymes were also induced; additional cationic isozymes are present in red oak and are influenced by galling insects in nature (Allison and Schultz, unpublished), but we were unable to resolve them completely on seedling IEF gels. Although the exact functions of anionic isozymes in red oak are unknown, their induction by wounding is consistent with responses to insects (Felton et al, 1992, Arnason et al, 1994, Dowd, 1994Dowd et al, 1998a,b). Anionic PODs have been implicated in a variety of leaftoughening responses, such as lignin biosynthesis (Gaspar et al, 1985;Díaz and Merino, 1998), suberization (Espelie et al, 1986;McDougall, 1993), and crosslinking of cell walls and extensin polymers (Ridge and Osborne, 1970;Everdeen et al, 1988;Bostock and Stermer, 1989).…”
Section: Discussionsupporting
confidence: 60%
“…The fact that protein content did not have a definite relationship with physical resistance parameters in this study may indicate that there are other resistance factors in maize studied. Arnason et al (1994;1997) reported the presence of biochemical compounds, particularly ferulic acid in the kernels.…”
Section: Discussionmentioning
confidence: 99%
“…The range of values of indices obtained in this experiment ( 0.77 to 9.11) was lower than those obtained by other investigators. Arnason et al (1994) obtained indices as high as 14 in susceptible varieties. One possible explanation is that the previous studies dealt with much more susceptible genotypes than in this experiment.…”
Section: Median Development Period (Mdp)mentioning
confidence: 92%
See 1 more Smart Citation
“…Maize (Zea mays L.), which is in the grass subfamily Panicoideae, is very diverse in its susceptibility to insects. For example, median duration of development of the maize weevil, Sitophilus zeamais Motschulsky, varied by 9.4 d, and the number of progeny produced varied by 265 individuals on 28 Mexican land races of maize (Arnason et al, 1994). The Pooideae occur mainly in temperate regions, while the Panicoideae occur mainly in subtropical and tropical regions.…”
Section: Discussionmentioning
confidence: 99%